2023
DOI: 10.3390/antiox12122040
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Superoxide Dismutase Attenuates Hepatic Oxidative Stress in Nonalcoholic Fatty Liver Disease through the Adenosine Monophosphate-Activated Protein Kinase Activation

Heechul Nam,
Ji Lim,
Tae Kim
et al.

Abstract: Oxidative stress is key in type 2 diabetes-associated nonalcoholic fatty liver disease (NAFLD). We explored whether extracellular superoxide dismutase (EC-SOD) activates adenosine monophosphate-activated protein kinase (AMPK) to enhance antioxidant synthesis and lipid metabolism in NAFLD. Human recombinant EC-SOD (hEC-SOD) was administered to 8-week-old male C57BLKS/J db/db mice through intraperitoneal injection once a week for 8 weeks. Target molecules involved in oxidative stress and lipid metabolism were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[34] Studies have shown that the activation of the AMPK/PGC-1α or AMPK/ Sirt3 signaling pathway in hepatocytes can regulate lipid metabolism, improve mitochondrial respiratory capacity and oxidation-reduction reaction homeostasis, reduce hepatic lipid accumulation and oxidative stress, and thus improve mitochondrial dysfunction. [35,36] Based on the above discussion, mtFAO deficiency is an important factor in lipid accumulation in the liver. MtFAO is a complex metabolic process, and its defects are not only manifested by reduced β-oxidation, OXPHOS-related gene or protein expression, and ATP synthesis, but also by the massive production of ROS and the resulting oxidative damage (Figure 1).…”
Section: Defect In Mitochondria Fatty Acid Oxidationmentioning
confidence: 98%
See 1 more Smart Citation
“…[34] Studies have shown that the activation of the AMPK/PGC-1α or AMPK/ Sirt3 signaling pathway in hepatocytes can regulate lipid metabolism, improve mitochondrial respiratory capacity and oxidation-reduction reaction homeostasis, reduce hepatic lipid accumulation and oxidative stress, and thus improve mitochondrial dysfunction. [35,36] Based on the above discussion, mtFAO deficiency is an important factor in lipid accumulation in the liver. MtFAO is a complex metabolic process, and its defects are not only manifested by reduced β-oxidation, OXPHOS-related gene or protein expression, and ATP synthesis, but also by the massive production of ROS and the resulting oxidative damage (Figure 1).…”
Section: Defect In Mitochondria Fatty Acid Oxidationmentioning
confidence: 98%
“…In MASLD, the expression of PGC-1α mRNA and sirt expression in the liver are reduced 34 . Studies have shown that the activation of the AMPK/PGC-1α or AMPK/Sirt3 signaling pathway in hepatocytes can regulate lipid metabolism, improve mitochondrial respiratory capacity and oxidation-reduction reaction homeostasis, reduce hepatic lipid accumulation and oxidative stress, and thus improve mitochondrial dysfunction 35,36 …”
Section: The Role Of Mitochondrial Dysfunction In Masldmentioning
confidence: 99%